Recent advances in palladium-catalyzed (hetero)annulation of CC bonds with ambiphilic organo(pseudo)halides - Ni, Hui-Qi; Cooper, Phillippa; Engle, Keary M. (Chemical communications (Cambridge, England), 2021)
Palladium has proven to be effective in catalyzing the (hetero)annulation of CC bonds with ambiphilic organo(pseudo)halides. Through the employment of appropriate ambiphilic coupling partners, efficient annulation of a variety of allenes, 1,3-dienes, strained alkenes, styrenes, and other CC bond variants can be achieved to provide direct access to numerous useful hetero- and carbocyclic scaffolds. In this Feature Article, we summarize palladium-catalyzed (hetero)annulation methods reported since 2005 (spanning just over 15 years) and discuss outstanding challenges in this area of study.